REMOTE RESULTS OF TREATMENT WITH FIXED DENTURES OF SENIOR PATIENTS WITH COMPLETE SECONDARY EDENTIA OF LOWER JAW WITH SUPPORT ON IMPLANTS - V.O. Ponomarenko; M.V. Khrebor; Yu.I. Silenko (Український стоматологічний альманах)
The aim of the work was to determine the effectiveness of treatment of elderly people with a complete secondary adentia with fixed constructions of dentures supported by three implants and cushioning abutments at different observation times. The use of cushioning abutments in patients with a high-pliable mucous membrane led to a significantly greater resumption of masticatory efficacy and a reduction in the atrophy of the tissues of the prosthetic bed. During the disintegration of one distally placed implant, the use of cushioning abutments was accompanied by the resumption of masticatory efficacy to similar parameters in patients who had prosthetics on four implants and rigid abutments.